Spontaneous heparin-induced thrombocytopenia presenting as bilateral adrenal hemorrhages and pulmonary embolism after total knee arthroplasty - Elshoury, Amro (Arthroplasty Today, 2015)
Heparin-induced thrombocytopenia syndrome is an acquired potentially life-threatening prothrombotic disorder caused by antibodies that recognize complexes of platelet factor 4 bound to heparin or heparin-like molecules. It typically occurs after exposure to unfractionated heparin, to a lesser extent after exposure to low-molecular-weight heparins, and rarely after exposure to fondaparinux. Herein, we report the case of a 48-year-old woman who developed severe thrombocytopenia, bilateral pulmonary embolism, and bilateral adrenal hemorrhages after total knee arthroplasty without evidence of heparin exposure. Antibodies to the heparin-platelet factor 4 complex and serotonin-release assay were positive. Spontaneous heparin-induced thrombocytopenia syndrome should be considered in patients with unexplained thrombocytopenia after knee replacement surgery even without heparin exposure, and a high index of suspicion for adrenal hemorrhage is needed in patients with fever, abdominal pain, and shock.